Revealing the influence of the solvent evaporation rate and thermal annealing on the molecular packing and charge transport of DPP(TBFu)2. Issue 21 (25th April 2016) - Han, Guangchao; Shen, Xingxing; Duan, Ruihong; Geng, Hua; Yi, Yuanping
Abstract : Correlation between charge mobility and molecular packing is revealed for the samples fabricated under different processing conditions via atomistic simulations. Abstract : By means of atomistic molecular dynamics simulations, we have investigated the effect of the solvent evaporation rate and thermal annealing on the molecular packing morphology of a diketopyrrolopyrrole based organic photovoltaic donor material, DPP(TBFu)2, which displays excellent hole mobility. It is observed that slow evaporation of solvent will lead to a relatively high degree of molecular packing order while leaving many voids in the as-cast sample. Upon thermal annealing, the as-cast samples at both fast and slow evaporation rates become more compact and much more apparently at the slow evaporation rate. Interestingly, the effect of thermal annealing on molecular packing order depends on the solvent evaporation rates of the as-cast samples. Upon thermal annealing, the molecular packing order of the fast evaporated sample is enhanced with increased π–π stacks. In contrast, thermal annealing will decrease the degree of packing order for the slow evaporated sample since the orientations and conformations of the molecules at the aggregate boundaries are substantially modulated to squeeze the voids. Electrical network analyses point to the fact that the mesoscopic electrical connectivities for all the samples are quite effective and insensitive to the modifications of local molecular ordering due to the delocalized HOMO of DPP(TBFu)2 providing efficient intermolecular electronic interactions. The hole mobilities of all the fabricated samples are thus estimated to be similar and quite high. Finally, our simulations point to the fact that the modest enhancement of mobility upon thermal annealing is correlated with the increased density rather than the varied ordering of molecular packing. Our work provides an atomistic insight into the evolution of thin-film morphology of organic photovoltaic molecular materials during solution processing and thermal annealing treatments and sheds light on the correlation between the molecular structure, packing morphology and hole transport capability.